English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

please help me to simplify...

a) (-x^3)(-x)^2(-x)
simplify. then evaluate the expression when x=2 and y=1
b) (-X)^4 (times) Y

2006-11-14 15:52:19 · 5 answers · asked by sonovabeeech 1 in Science & Mathematics Mathematics

5 answers

When multiplying terms with exponents you multiply the terms and add the exponents.

a)
(-x^3)(-x^2) = x^5 because neg * neg = pos and 2 + 3 = 5

a term without an exponent is assumed to have an exponent of 1 therefore (x^5)(-x) = -x^6

b)
-2(-2) = 4, 4(-2) = -8, -8(-2) = 16

2006-11-14 16:28:05 · answer #1 · answered by ikeman32 6 · 0 0

a) just add the exponents = 3+2+1 = 6

(-x)^3(-x)^2(-x)
(-x)^6 or x^6

b) (-x)^4 * y
x^4 y
(2)^4 *1
16*1
16

2006-11-15 00:12:43 · answer #2 · answered by tma 6 · 0 0

do your own homework. I graduated high school so I'd never have to look at things like this ever again.

2006-11-14 23:56:20 · answer #3 · answered by Anonymous · 0 1

a)
(-1)(-1)(-1) = -1
(x^3)(x^2))(x) = x^6
(-x^3)(-x)^2(-x) = -x^6
= -(2^6) @ x = 2

b)
(-x)^4y @ 2,1 = 1*(-2)^4

2006-11-15 00:02:23 · answer #4 · answered by Helmut 7 · 0 1

a)(-8)(4)(-2)=64
b)16

2006-11-15 00:20:37 · answer #5 · answered by an_inflection 2 · 0 0

fedest.com, questions and answers